2021
DOI: 10.1016/j.micres.2020.126643
|View full text |Cite
|
Sign up to set email alerts
|

Altered bacteria community dominance reduces tolerance to resident fungus and seed to seedling growth performance in maize (Zea mays L. var. DKB 177)

Abstract: Seeds are reservoirs of beneficial and harmful microorganism that modulates plant growth and health. Here, we access seed to seedling bacteriome assembly modified by seed-disinfection and the underlined effect over maize germination performance and root-seedlings microbial colonization. Seed-disinfection was performed with sodium hypochlorite (1.25%, 30 min), resulting in a reduction of the cultivable-dependent fraction of seed-borne bacteria population, but not significantly detected by real-time PCR, microsc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Vertical transmission across generations has a profound impact on plant ecology. However, few studies are linking the diversity of endophytic bacteria in maize seeds with generational transmission, and most studies tend to be female parents (Santos et al, 2021). Based on the traditional separation method, this study found that Bacillus and Pantoea were the dominant bacteria of maize and the pollen at the genus level.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Vertical transmission across generations has a profound impact on plant ecology. However, few studies are linking the diversity of endophytic bacteria in maize seeds with generational transmission, and most studies tend to be female parents (Santos et al, 2021). Based on the traditional separation method, this study found that Bacillus and Pantoea were the dominant bacteria of maize and the pollen at the genus level.…”
Section: Introductionmentioning
confidence: 82%
“…As a medium for carrying and transmitting plant genetic information, plant seeds also contain abundant endophytic bacteria resources (Wang et al, 2021). Santos et al (2021) found that the germination rate of seeds with surface disinfection was signi cantly lower than that of the control group. The endophytic bacteria in the seeds coordinated the microbial balance of the seeds and promoted corn germination and seedling growth.…”
Section: Introductionmentioning
confidence: 99%
“…Many different microbes can grow in seed, and the maize seed community is distinct from other parts of the plant (Johnston‐Monje & Raizada, 2011 ). Only a handful of studies have looked at the maize seed endophyte community with modern deep sequencing methods (Johnston‐Monje et al, 2021 ; Liu et al, 2017 , 2020 ; Majumdar et al, 2021 ; Santos et al, 2021 ), so most of our knowledge comes from isolation studies. However, based on both sequencing (Figure 1 ) and isolation (Tables 1 and 2 ), the bacteria of the maize seed are dominated by Proteobacteria, Actinobacteria, and Firmicutes, with the majority of fungi placed in the Ascomycota phylum.…”
Section: What Microbes Are In Maize Seeds?mentioning
confidence: 99%
“…Transmission across multiple generations (see below) implies they must at least be in the stalk and aboveground vasculature. Electron microscopy of sterile, germinating seeds shows microbes in the pericarp, endosperm, radicle, and germinating root surface (Santos et al, 2021 ), and the beneficial microbe B. mojavensis RCC101 was seen to cover the root epidermis after germination (Bacon et al, 2001 ). The presence of endophytes on the root surface implies that microbes can move from the seed out into the rhizoplane and rhizosphere, a conclusion supported by other work (Johnston‐Monje & Raizada, 2011 ; White et al, 2019 ).…”
Section: Where Are Seed Endophytes?mentioning
confidence: 99%